Modern studies democracy in Scotland and the UK - Cooney, Frank; Hughes, Gary; Sheerin, David (Hodder Gibson, 2021)
Exam Board: SQA Level: Higher Subject: Modern Studies First Teaching: August 2018 First Exam: June 2019 A course textbook covering the most recent political developments and fully updated to take on board the latest SQA course assessment changes. Written specifically to match the Higher syllabus offered by the Scottish Qualifications Authority, Democracy in Scotland and the UK covers all of the topics that students will encounter in this unit of the course: UK constitutional arrangements, representative democracy and the political process, electoral systems and voting behaviour. - Questions to help monitor progress throughout the topics - Case studies and fact files to focus attention on specific areas - Assessment guides to prepare students for the final exam.